2018
DOI: 10.1111/jace.15939
|View full text |Cite
|
Sign up to set email alerts
|

Hydration mechanisms of hybrid cements as a function of the way of addition of chemicals

Abstract: In this study fly ash contents of up to 50% were used to produce binders with mechanical strength greater than or equal to type CEM I 42.5R cement (reference). The specific aim pursued in this research was to determine whether the procedure used to add the chemical activator (in solid or liquid form) can affect strength development in the cement or the nature of the reaction products formed. Two experimental procedures were deployed: (a) the chemical activator was dissolved in the mixing water; (b) the chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(40 citation statements)
references
References 35 publications
(55 reference statements)
0
36
0
4
Order By: Relevance
“…Previous studies have demonstrated a significant increase in the overall reactivity and mechanical properties, when high volume fly ash blends are activated with Na 2 SO 4 . [1][2][3][4][5] However, the current understanding of the effect of Na 2 SO 4 on the hydration of Portland cement systems is rather limited, and new knowledge is required to understand the fundamental mechanisms, potentials, and limitations of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have demonstrated a significant increase in the overall reactivity and mechanical properties, when high volume fly ash blends are activated with Na 2 SO 4 . [1][2][3][4][5] However, the current understanding of the effect of Na 2 SO 4 on the hydration of Portland cement systems is rather limited, and new knowledge is required to understand the fundamental mechanisms, potentials, and limitations of such systems.…”
Section: Introductionmentioning
confidence: 99%
“…The difference may be attributed to the formation of a smaller amount of hydrates in the HYC, particularly AFm and AFt phases and of hydrates with less water in their structure. C-S-H gels are deemed to take up more water in their structure than C-A-S-H or N-A-S-H gels (24). The endothermal peak at 430 °C to 450 °C related to portlandite dehydroxylation (1, 3) was much more intense in OPC than in HYC (Figure 3), an indication that more portlandite formed in the former than in the latter.…”
Section: Tg and Dtamentioning
confidence: 97%
“…Hybrid alkaline cements (HYCs) are a new group of cements, developed by combining knowledge of traditional Portland and alkaline cement chemistry (11,(20)(21)(22)(23)(24). They are characterised by low clinker content (20 % to 30 %) and a high proportion of supplementary cementitious materials (SCMs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the promising ways for comprehensive disposal of industrial wastewater treatment products is to use them as components for water mixing and for the filler of alkaline cements [7]. These materials have unique performance properties, and include in their composition to 95 % of waste and related industrial products (fuel ash [8], blast furnace granulated slags [9], etc.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%